(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Generic drugs, which are therapeutically equivalent to brand-name drugs in terms of dosage, safety, strength, quality, and performance, have gained significant traction since the enactment of the 1984 Hatch-Waxman Act in the United States. This legislation facilitated the streamlined approval of generics through the Abbreviated New Drug Application (ANDA) process, eliminating the need for costly preclinical and clinical trials. Generics offer a cost-effective alternative to branded medicines, especially in countries like India, where a large portion of healthcare expenses are paid out-of-pocket. India’s Jan Aushadhi initiative exemplifies efforts to expand access to affordable generics; however, challenges remain in scaling distribution and maintaining consistent drug quality. Despite their affordability, concerns persist regarding the quality and bioequivalence of some generic formulations, which can undermine public trust. Strengthening regulatory oversight, enhancing quality assurance mechanisms, and improving medical education on generic prescribing are critical to increasing acceptance and usage. A coordinated strategy combining regulation, education, and quality control can drive broader adoption of generics and play a vital role in reducing global healthcare costs.